MENUMBUHKAN SIKAP GEMAR SAAT TEDUH PAGI SETIAP HARI MELALUI APLIKASI ZOOM DI LINGKUNGAN JEMAAT GKRI DIASPORA RAFA MEDAN - Benny Andreson Situmorang; Dina Sembiring (JOURNAL OF COMMUNITY DEDICATION, 2024)
This research aims to foster an attitude of liking daily morning quiet time through the zoom application within the GKRI Diaspora Rafa Congregation in Medan. As a disciple of Jesus, the attitude of enjoying morning devotions is a very important attitude for God's people to carry out in building a good relationship with God. The research/research method carried out consists of several stages. Each stage includes planning, implementation, observation, and reflection. The results of the research show that by using the zoom method for quiet time which is interactive and interesting and varied, officers take turns, reading God's Word together, responsoria, and discussions, sharing prayer topics and praying together there was a significant increase in interest and frequency of participating in quiet time with the GKRI Diaspora Rafa Medan ministry team and congregation. Apart from that, cooperation between the pastor and the entire assembly is very supportive in encouraging an attitude of enjoying quiet time. The conclusion of this research is that the application of varied and collaborative quiet time methods fosters an attitude of liking quiet time for the GKRI Diaspora Rafa Medan congregation. Recommendations for further research are to expand the methods used and involve more participants from the congregation to create a strong commitment in morning devotional time.